Basic environmental health - Annalee Yassi (Oxford University Press, 2001)
This comprehensive interdisciplinary text draws from the social sciences, the natural sciences and the health sciences to introduce students to the principles and methods applied in environmental health. It presents an overview of the basic sciences needed to understand environmental health hazards, including toxicology, microbiology, health physics, injury analysis and relevant psychosocial concepts. It also presents a basic approach to risk assessment and risk management. The first part of the book concentrates on broad issues, providing frameworks for the investigation and management of environmental health problems. The middle section deepens the discussion of routes of exposure (air quality, water and sanitation, food and agricultural issues). The final section addresses environmental health from sustainable development themes (settlements and urbanization, energy, industry, and global concerns). The final chapter focuses on ethical issues and action planning. Thus, the text aims to enhance knowledge, skills and attitudes in environmental health